1985
DOI: 10.1111/j.1439-0442.1985.tb01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathophysiological Features of Granulomatous Enteritis and Eosinophilic Granulomatosis in the Horse

Abstract: Summary The interrelationships between clinical, clinicopathological and morphological findings were studied in 17 cases of equine granulomatous enteritis (GE) and 19 cases of equine eosinophilic granulomatosis (EG) in order to define criteria for clinical diagnosis and to elucidate pathophysiological events in these disorders. Both diseases were marked by progressive wasting and hypoalbuminaemia. They occurred sporadically and showed a predilection for 1‐ to 4 year‐old standardbreds. Excessive protein loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 14 publications
(9 reference statements)
1
71
0
3
Order By: Relevance
“…In general, MEED is a slowly progressive, chronic disease affecting young horses and most often standardbreds and quarter horses (Lindberg et al 1985;Schumacher et al 2000). To our knowledge, this is the first report of a horse with an acute progression of MEED.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In general, MEED is a slowly progressive, chronic disease affecting young horses and most often standardbreds and quarter horses (Lindberg et al 1985;Schumacher et al 2000). To our knowledge, this is the first report of a horse with an acute progression of MEED.…”
Section: Discussionmentioning
confidence: 77%
“…Possible explanations for the quick deterioration of the horse are the presence of severe lesions of the bile ducts, the pancreatic ducts and the intestines and the presence of high fever. Only three previously reported cases have described the presence of fever (Lindberg et al 1985;Platt 1986;Sweeney et al 1986 The majority (95%) of 44 horses previously reported with MEED presented with severe weight loss and 55% had concurrent, sometimes intermittent diarrhoea. In the present case, the severe weight loss and diarrhoea was apparently caused by severe diffuse eosinophilic enteritis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Suggested aetiologies include bacterial, viral, toxic, type 1 hypersensitivity (diet, inhaled, parasitic antigens) and immune‐mediated causes as well as eosinophilopoietic cytokines from activated or neoplastic T‐lymphocytes (Pass and Bolton ; Lindberg et al . ; Nimmo Wilkie et al . ; Sanford ; La Perle et al .…”
Section: Discussionmentioning
confidence: 99%
“…If this delicate balance is interrupted, a state of chronic uncontrolled inflammation may ensue (German et al 2003). A syndrome, marked by chronic weight loss and hypoalbuminaemia associated with chronic gastrointestinal disorders is well known in Standardbreds with two different pathomorphological entities, namely eosinophilic granulomatosis and granulomatous enteritis (Lindberg et al 1985). Lymphocytic-plasmacytic enteritis also belongs to this complex of equine idiopathic inflammatory small bowel disease (ISBD).…”
Section: Introductionmentioning
confidence: 99%